The wrath of Darth Maul - Windham, Ryder (Scholastic, 2012)
A villain profile for middle-grade Star Wars fans introduces the notorious Darth Maul, tracing the story of his embrace of the dark side through his eventual defeat, in a portrait that also reveals previously undisclosed character secrets.